Functional aquatic ecosystems, inland fisheries and the Millennium Development Goals. Issue 3 (24th April 2012) - Brummett, Randall E; Beveridge, Malcolm C M; Cowx, Ian G
Abstract: Freshwater allocation in an environment of increasing demand and declining quality and availability is a major societal challenge. While biodiversity and the needs of local communities are often in congruence, the over‐riding necessity of meeting national demands for power, food and, increasingly, mitigation of the hydrological effects of climate change, often supersedes these. Sophisticated models of ecosystem function to establish environmental flows are difficult to implement and consequently have generally failed to reduce rates of biodiversity and habitat loss, resulting in disenfranchisement of local communities resulting from dam construction and water abstraction for industry and agriculture. There are no agreed standards upon which a fairer allocation of resources can be made and thus a pragmatic approach to the resolution of these conflicts is clearly needed. While having generally negative impacts on biodiversity and traditional lifestyles, creation of new infrastructure and active management generates national economic growth and much‐needed employment. Intensification of usage in watersheds already expropriated for human enterprise can spare land needed for the biodiversity that will fuel adaptation for the future. Taking advantage of a range of mitigation technologies and building their cost into the investment plans for water management infrastructure can improve the cost/benefit ratio of water control infrastructure and may be a more practical and efficacious approach to the valuation of fisheries and the maintenance of other essential services from functional aquatic ecosystems.